P115 Improved reporting of vertebral fractures by radiologists: a success story!. (26th April 2021) - Nazir, Muhammad Amjad; Jamal, Muhammad Safwan; Hart, Darren; Shipley, Jacqueline; Warren, Susie; Hardcastle, Sarah; Ahmed, Tehseen
Abstract: Background/Aims   Vertebral fractures (VF) are the most common type of osteoporotic fracture and affect >20% women over the age of 80. However, the majority remain undiagnosed. Even when imaging has been performed, VF are under-reported by radiologists. This results in a missed opportunity for treatment to reduce fracture risk and morbidity. We conducted this project to improve the reporting of VF (incidental or symptomatic), thus enabling our fracture liaison service to identify cases more easily and optimise patient care. Methods   Using SYNAPSE (imaging software), cohorts of patients aged more than 75 years of age who had CT scans of chest/abdomen/pelvis in 2012 and 2017 were selected. Images were reviewed by a single rheumatologist with an interest in osteoporosis, looking for the presence of VF. For patients with VF, radiology reports were reviewed to assess whether there was documentation of this. Results   There was improvement in the reporting of VF between 2012 and 2017 (see Table 1 ) but identification remained suboptimal. Specific use of the term "fracture" remained in the minority. The data was presented to our radiologists in December 2017 along with information about the importance of identifying and treating patients with VF. Agreement was reached for the radiologists to include a code (FLS) in reports where a non-pathological VF was identified. Searches for the presence of the code through the hospital's radiology information system have allowed easy identification of VF cases. Letters are sent to Primary Care teams informing them that we have identified an incidental VF along with suggested management advice. This project has substantially increased the number of VF identified (in patients aged >50) by our fracture liaison service over time. 82 cases of VF were identified in 2017 (pre-intervention), 350 cases in 2018, and 848 cases in 2019. Conclusion   Collaboration with our radiologists through education and the use of a code in radiology reports has resulted in a sustained and dramatic increase in the number of VF annually identified by our fracture liaison service. We strongly recommend that other services adopt this approach to help them achieve national audit targets and improve patient care. Disclosure   M. Nazir: None. M. Jamal: None. D. Hart: None. J. Shipley: None. S. Warren: None. S. Hardcastle: None. T. Ahmed: None.